Search for heavy stable charged particles in the CMS experiment using the RPC detectors (2010)
In this work the results of a search for heavy stable charged particles in proton proton collisions at a center-of-mass energy of 7 TeV is presented. The search was performed with the CMS detector at the CERN LHC accelerator using the data from the 2010 run. The RPC detectors of the Muon System of CMS were used to recon struct tracks consistent with massive and slow-moving charged particles, using what is know as the time-of-flight technique. These particles are predicted by several theoretical scenarios beyond the Standard Model that include long-lived massive charged particles as part of their spectrum, for instance different flavors of supersymmetry, universal extra-dimension models etc. These charged particles can be hadrons that have long-lived gluinos or stops in their partonic content, known as R-Hadrons. The integrated luminosity of the LHC during the 2010 run and the predicated cross sections for this kind of states indicate that only R-Hadrons and staus could be observed. The R-Hadrons can be result of long-lived stops predicted by the Minimal Supersymmetric Standard Model or long-lived gluinos predicted by split SUSY.The staus can be the result of the Minimal Supersymmetric Standard Model with minimal gauge mediated symmerey breaking. Since these particles are massive and have electric charge, they behave as slow muons, being very penetrating and leaving traces in the detectors, therefore they can be registered by the Muon System of CMS. The CMS RPCs record timing information for these tracks allowing for the estimation of the speed B. The curvature of the tracks in the CMS magnetic field is used for the determination of the momentum p of the particle. Given B and p, the mass of the state can be determined. States with mass of the order of hundreds of GeV represent the discovery of physics beyond the Standard Model. The first run of the LHC finished on October 28 2010, the LHC has delivered a total integrated lumonisity of 46.36 pb -¹, Using the certified data (30.68 pb-¹ by November 7) and the RPC time-of-flight technique, limits on the mass for HSCPs predicted by three theoretical models were set with 95% of confidence level (split-SUSY gluino: 299.5 GeV/c², MSSM s-top: 167.5 GeV/c² and mGMSB SUSY stau: 107.5 GeV/c², MSSM s-top: 167.5 GeV/c² and mGMSB SUSY stau: 107.5 GeV/c²). The complete set of results and a detailed description of the analysis are presented in this document